Ramifications of Varying Islamic Banking Regulations on Performance of Islamic Banks - Zainuddin, Sara Sophia (2016)
Banking regulations imposed play a crucial role on the performance of banks, it could either encourage banks to perform better or encourage banks to engage in unnecessary risky investment activities for the sake of lucrative returns without adding any value to the economy. Implementation of non-suitable regulations could also impair banks’ performance, for instance, Islamic banks adopting standards that are meant for conventional banks. This paper analyses whether adopting Islamic banking regulations and frameworks has any significant impact on Islamic banks’ performance. For comparing purposes, two regions were selected in this paper which is the Gulf Cooperation Council (GCC) region and the region of South/Southeast Asia (SSA). The aim of this study is to observe how similar selected determinants can behave differently under different regions. This paper employs the two-step Generalized Methods of Moments technique to conduct the estimations. Findings suggest that Islamic regulatory variables are only positively significant with Islamic banks’ performance in the SSA region while it is not relevant in the GCC region. Results also suggest that high-performing Islamic banks in GCC region are able to contain the adverse effects of under developed stock markets better than Islamic banks that are operating below average. In addition, high-performing Islamic banks in SSA region that are well capitalized tend to benefit from a slightly more favourable effect on their performance.